Решить уравнение:

1 – х – х в квадрате = х – (х – 2) (х + 3) .

Лёва9898 Лёва9898    2   14.02.2020 11:32    0

Ответы
Teacher991 Teacher991  11.10.2020 04:38

1-x-x²=x-(x-2)(x+3)

1-x-x²= x-x²-3x+2x+6

1-x-x+3x-2x-6=0

-x-5=0

x= -5

ПОКАЗАТЬ ОТВЕТЫ
proxiv proxiv  11.10.2020 04:38

х=7

Объяснение:

убрать равные слагаемые, раскрыть модуль

-1-х^2= -(х^2+3х-2х-6)

привести подобные

-1-х^2= -(х^2+х-6)

раскрыть скобки

-1х^2= -х^2-х+6

убрать равные слагаемые

-1=-х+6

перенести х в другую часть уравнения

х=6+1

х=7

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра